Pengembangan Kapasitas Kelompok Tani dalam Penerapan Pertanian Terpadu di Nglebak, Karanganyar - Nurul Huda (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2021)
ABSTRACT Capacity development is an effort to increase the potential that is owned, leading to increased knowledge and abilities. The hope is that it will raise social attitude, change behavior for the better, and be independent. This study aims to1) analyze the implementation of capacity building for farmer groups, and 2) analyze the supporting and inhibiting factors in capacity building. This research users qualitative research with a descriptive approach. The types of data used are primary and secondary data obtained from observation, interactive analysis by Miles and Huberman, while the data validity technique used source triangulation and method triangulation. The results showed that the capacity building activities carried out were routine meetings, organic farming, communal shed management, fertilizer production, and trainings. Supporting factors in this research are land availability, farmer characteristics, social capital, group partnerships, institutional support or external parties. Inhibiting factors in this study were limited capital, not optimal organic farming, not optimal cattle breeding, difficulty marketing and low organic vegetables.